Речевое воздействие: ракурсы адресанта и адресата - Шелестюк Елена Владимировна (Психолингвистика, 2008)
Экземпляры: СЭ (20110204) / Инвентарный номер: 1082512 / Цена: / Сис.шифр: 88.3 / Авт.знак: Ш 42 / ГРНТИ: 16.21.29 / ББК: 88.351.32